Uji Aktivitas Antibakteri Ekstrak Etanol Daun Mangga Arum Manis (Mangifera indica L.var arum manis) terhadap Staphylococcus epidermidis - Ida Ayu Rati Sunari; Musyarrafah Musyarrafah; Herlinawati Herlinawati; Halia Wanadiatri (Malahayati Nursing Journal, 2025)
ABSTRACT The development of natural materials, in this case phytochemical compounds from herbal plants, is utilized as antibiotic agents in dealing with several cases of antibiotic resistance. Arum manis mango plant (Mangifera indica L. var arum manis) is one of the species of the mango family that is widely distributed in Indonesia and has many benefits ranging from fruit, seeds, fruit skin, leaves and stems. Arum manis mango leaves contain flavonoids, alkaloids, steroids, polyphenols, tannins, and saponins which have the ability to inhibit bacterial growth. To determine the antibacterial activity of ethanol extract of arum manis mango leaves on the growth of Staphylococcus epidermidis bacteria. True Experiment with Posttest Only Control Group Design using the well method. The research subjects amounted to 24 samples divided into 4 treatment groups, namely ethanol extract of arum manis mango leaves with concentrations of 25%, 50%, 75%, 100% and 2 controls (positive control ciprofloxacin and negative control aquadest). The data obtained was analyzed using SPSS version 27. The results of the bivariate test showed a significant difference (p-value 0.05) in the inhibition zone of the treatment group with positive and negative controls (Staphylococcus epidermidis, p-value 0.001). The average inhibition zone formed in the ethanol extract group of arum manis mango leaves on Staphylococcus epidermidis is concentrations of 25% (15.87 mm); 50% (18.25 mm); 75% (19.62 mm) and 100% (20.37 mm). There is antibacterial activity of the ethanol extract of arum manis mango leaves (Mangifera indica L. var arum manis) against the growth of Staphylococcus epidermidis bacteria. Keywords: Antibacterial, Arum Manis Mango Leaves, Staphylococcus Epidermidis, Wells  ABSTRAK Pengembangan bahan alam dalam hal ini senyawa fitokimia dari tanaman herbal dimanfaatkan sebagai agen antibiotik dalam menangani beberapa kasus resistensi antibiotik. Tanaman mangga arum manis (Mangifera indica L. var arum manis) merupakan salah satu spesies dari famili buah mangga yang banyak tersebar di wilayah Indonesia dan memiliki banyak manfaat mulai dari buah, biji, kulit buah, daun dan batangnya. Daun mangga arum manis mengandung senyawa flavonoid, alkaloid, steroid, polifenol, tannin, dan saponin yang memiliki kemampuan menghambat pertumbuhan bakteri. Mengetahui aktivitas antibakteri ekstrak etanol daun mangga arum manis terhadap pertumbuhan bakteri Staphylococcus epidermidis. True Experiment dengan Posttest Only Control Group Designmenggunakan metode sumuran. Subjek penelitian berjumlah 24 sampel dibagi ke 4 kelompok perlakuan, yaitu ekstrak etanol daun mangga arum manis konsentrasi 25%, 50%, 75%,100% dan 2 kontrol (kontrol positif ciprofloxacin dan kontrol negatif aquadest). Data yang didapatkan dianalisis menggunakan SPSS versi 27. Hasil dari uji analisis data menunjukan terdapatnya perbedaan bermakna (p-value 0,05) zona hambat kelompok perlakuan dengan kontrol positif dan negatif (Staphylococcus epidermidis, p-value 0,001). Rata-rata zona hambat yang terbentuk pada kelompok ekstrak etanol daun mangga arum manis pada Staphylococcus epidermidis konsentrasi 25% (15,87 mm); 50% (18,25 mm); 75% (19,62 mm) dan 100% (20,37 mm). Terdapat aktivitas antibakteri ekstrak etanol daun mangga arum manis (Mangifera indica L. var arum manis) terhadap pertumbuhan bakteri Staphylococcus epidermidis. Kata Kunci: Antibakteri, Daun Mangga Arum Manis, Staphylococcus Epidermidis, Sumuran